WIde Separation Planets In Time (WISPIT): A Gap-clearing Planet in a Multi-ringed Disk around the Young Solar-type Star WISPIT 2 - Richelle F. van Capelleveen; Christian Ginski; Matthew A. Kenworthy; Jake Byrne; Chloe Lawlor; Dan McLachlan; Eric E. Mamajek; Tomas Stolker; Myriam Benisty; Alexander J. Bohn; Laird M. Close; Carsten Dominik; et al. (The Astrophysical Journal Letters)
In the past decades, several thousand exoplanet systems have been discovered around evolved, main-sequence stars, revealing a wide diversity in their architectures. To understand how the planet formation process can lead to vastly different outcomes in system architecture, we have to study the starting conditions of planet formation within the disks around young stars. In this study, we are presenting high-resolution direct imaging observations with the Very Large Telescope/SPHERE of the young (∼5 Myr), nearby (∼133 pc), solar-analog designated as WISPIT 2 (= TYC 5709-354-1). These observations were taken as part of our survey program that explores the formation and orbital evolution of wide-separation gas giants. WISPIT 2 was observed in four independent epochs using polarized light and total intensity observations. They reveal for the first time an extended (380 au) disk in scattered light with a multi-ringed substructure. We directly detect a young protoplanet, WISPIT 2b, embedded in a disk gap and show that it is comoving with its host star. Multiple SPHERE epochs demonstrate that it shows orbital motion consistent with Keplerian motion in the observed disk gap. Our H - and K _s -band photometric data are consistent with thermal emission from a young planet. By comparison with planet evolutionary models, we find a mass of the planet of $4.{9}_{-0.6}^{+0.9}$ M _Jup . This mass is also consistent with the width of the observed disk gap, retrieved from hydrodynamic models. WISPIT 2b is the first unambiguous planet detection in a multi-ringed disk, making the WISPIT 2 system the ideal laboratory to study planet–disk interaction and subsequent evolution.